Numerical study of fatigue crack initiation and propagation on optimally designed cruciform specimens - Baptista, R. (2016)
A new generation of smaller and more efficient biaxial fatigue testing machines has arrived on the market. Using electrical motors these machines are not able to achieve the higher loads their hydraulic counterparts can, and therefore the cruciform specimen needs to be optimized Following the authors previous work, several different optimal specimens' configurations were produced, using the base material sheet thickness as the main design variable. Every design variable was optimized in order to produce the highest stress level on the specimen center, while the stress distribution is still uniform on a 1 mm radius of the specimen center. Also it was guaranteed that the stress level on the specimen arms was always considerably lower, in order to achieve failure at the specimen center. In this paper traditional criteria like Findley, Brown-Miller, Fatemi-Socie, Smith, Watson e Topper (SWT), Liu I and Chu were considered to determine crack initiation direction for several loads in this biaxial in-plane specimens. In order to understand the fatigue propagation behavior, the stress intensity factors for mode I and mode II was determined for different cracks introduced on the geometry. Several crack and loading parameters were studied, including the starting crack length and angle, and different loading paths. Several biaxial loads were applied to the model, including 30, 45, 60, 90 and 180 out-of-phase angles.